The Efficacy of Rehearsal Strategy on Visual Short-Term Memory of Children with Down Syndrome - Gita Sadighi; Sahel Hemmati; Esmail Esmaili; Masoumeh Pourmohamadreza-Tajrishi (Vesnu Publications, 2016)
Introduction: Down syndrome is the most common genetic cause (22% on average) of learning disability. Individuals with Down syndrome show deficits in working memory which is responsible for the storage of information and plays an important role in learning. The aim of this study was to determine the efficacy of rehearsal strategy on visual short-term memory of educable children with Down syndrome and of 5 to 8 years of age. Materials and Methods: In this quasi-experimental study, after obtaining the consent of their parents, 24 children from the Iranian Down Syndrome Charity Association were chosen through convenience sampling, and then, evaluated using Raven's Progressive Matrices. The children were randomly allocated to experimental and control groups. The experimental group participants were taught rehearsal strategy in 8 group sessions. All children were assessed using the visual memory sequence test before and after the intervention. Data were analyzed using single-factor ANCOVA. Results: The results of ANCOVA showed that rehearsal strategy increased digit and word span and improved visual short-term memory (P < 0.001) in children who received the intervention in comparison with the control group. Conclusion: This study reflects that rehearsal strategy is one of the main methods that can be used to improve the quality of visual short-term memory of children with Down syndrome.